Influência da separação da fração sólida-líquida de dejeto de codornas na produção de metano - Bastos, Jhenifer Aline (2019)
The use of techniques applied to the handling of animal substrates allows the concentration of solids or preliminary processes of separation of the solid and liquid fraction. Gravity decanting is an attractive option for separation because it presents low cost and use of simple technologies, being able to be operated continuously or in batch. However, the objective of this work was to evaluate the difference in methane production obtained by solid and liquid fractions of quails using the screening and gravity sedimentation method. Samples were collected at two points from a quail egg production site located in the eastern part of Santa Catarina State, where the storage point was the ejection point and the washing effluent from the poultry packing sites used to feed the biodigester. For the separation of the solid-liquid phases, a sieve (holes <2 mm) was used to obtain the solid fraction and the Hinhoff cone, for the liquid fractions (supernatant and decanted). The characterization was performed to obtain the total solids content (ST), volatile solids (SV) and pH. The Biochemical Metanogenic Potential (BMP) was carried out in glass flasks with a capacity of 100 mL, being 50% of the volume of the headspeace, according to the conditions established by the standard VDI 4630 (2006). The supernatant fraction presented the highest value of methane production based on the volatile solids content (422 ± 3 LN CH4 kg SV-1) and the lower methane production based on the natural matter content (56 (LN CH4 kg MN-1 ), While the crude manure (214 ± 18 LN CH4 kg MN-1) was 74% higher than SF, showing the best conversion efficiency of the biodegradable matter in methane.